Grid portal for bioinformatics sequences alignment applications / Azlan Arifin - Azlan , Arifin (2008)
The aim of present study is to develop a grid portal for bioinformatic’s sequences alignment applications. Further enhancement has been done to the campus grid called GeRaNIUM. A web-based interface called GeRaNIUM Grid Portal (GGP) was successfully developed and implemented on GeRaNIUM to provide a simple user friendly interface for grid users with varying IT experience. This Portal allows grid users to submit jobs in a secure, reliable and scalable manner. However, most of bioinformatic’s users are hesitant to run a parallel job in a grid environment. In order to convince users to use parallel computing in grid environment, a comparison study has been done to compare the performance of process runtime among workstation and cluster computing in the GeRaNIUM grid environment. The main comparison was based on process runtime and consistency of results produced. The produced results in this study have shown that output consistency is achieved while the computing speed is increased in the grid environment. Findings of this study indicated that parallel computing could speed up the runtime of Bioinformatics applications by parallelizing the sequences alignment process into collective resources. Besides, parallel computing not only accelerated the process but also produced reliable outputs which might convince users to use parallel computing. The runtime on different problem sizes showed that parallel computing was more effective on running problems that had shorter length of sequences rather than processing a longer length of sequences. The main contribution in this project was the development of Grid portal which would make it easier for a GeRaNIUM user to exploit grid applications anytime and anywhere.